Never Innocent Victims: Street Sex Workers in Canadian Print Media. (January 2014) - Strega, Susan; Janzen, Caitlin; Morgan, Jeannie; Brown, Leslie; Thomas, Robina; Carriére, Jeannine
Over the past decade, street sex workers and their families garnered considerable media attention through extensive coverage of disappeared and murdered women in Western Canada. The research presented here examines whether recent media accounts differ from past coverage given that families and friends of disappeared and unaccounted for women inserted themselves into media discussions and circulated alternative readings of their stories. We found that coverage was dominated by two discourses: Vermin-victim discourse demonstrates the tensions between historically dominant conceptualizations and more recent ideas promulgated by families; and risky lifestyle discourse is related to neo-liberal ideologies about personal choice and responsibility.